Assessing the Load, Virulence and Antibiotic-Resistant Traits of ESBL/Ampc E. coli from Broilers Raised on Conventional, Antibiotic-Free, and Organic Farms - Silvia Tofani; Elisa Albini; Francesca Blasi; Lucilla Cucco; Carmela Lovito; Carmen Maresca; Michele Pesciaroli; Serenella Orsini; Eleonora Scoccia; Giovanni Pezzotti; Chiara Francesca Magistrali; Francesca Romana Massacci (MDPI AG, 2022)
Poultry is the most likely source of livestock-associated Extended Spectrum Beta-Lactamase (ESBL) and plasmid-mediated AmpC (pAmpC)-producing E. coli (EC) for humans. We tested the hypothesis that farming methods have an impact on the load of ESBL/pAmpC-EC in the gut of broilers at slaughter. Isolates (n = 156) of antibiotic-free (AF), organic (O), and conventional (C) animals were characterized for antibiotic susceptibility and antibiotic resistance genes. Thirteen isolates were whole-genome sequenced. The average loads of ESBL/pAmpC-EC in cecal contents were 4.17 Log CFU/g for AF; 2.85 Log CFU/g for O; and 3.88 Log CFU/g for C type (p < 0.001). ESBL/pAmpC-EC isolates showed resistance to antibiotic classes historically used in poultry, including penicillins, tetracyclines, quinolones, and sulfonamides. Isolates from O and AF farms harbored a lower proportion of resistance to antibiotics than isolates from C farms. Among the determinants for ESBL/pAmpC, CTX-M-1 prevailed (42.7%), followed by TEM-type (29%) and SHV (19.8%). Avian pathogenic E. coli (APEC), belonging to ST117 and ST349, were identified in the collection. These data confirm the possible role of a broiler as an ESBL/AmpC EC and APEC reservoir for humans. Overall, our study suggests that antibiotic-free and organic production may contribute to a reduced exposure to ESBL/AmpC EC for the consumer.